Financing of university campus projects in Russia - I. N. Rykova; T. S. Remizova; R. S. Gubanov; M. O. Ivanov (Вестник Северо-Кавказского федерального университета)
The projects for the creation of university campuses at the present stage of Russia's development reflect the priorities of the implementation of scientific and technological initiatives approved at the level of the subjects of the Russian Federation, specific enterprises of the real sector of the economy and require the analysis of the impact on the national economy. However, for the development of a network of university campuses, large-scale financing of these projects is necessary; the systematization of sources of financing for the creation of university campuses in Russia is the purpose of this study. Materials and methods of research. The article used materials of normative legal support for the creation of university campuses, analyzed Russian literature sources, and applied methods of logical generalization, systematic observation, and analytical approach. Research results and their discussion. The paper presents the organizational and economic foundations for the creation and financing of a new type of campuses at universities in Russia, gives the concept and essence of a university campus - as an open educational space with a complex of infrastructure facilities for the purposes of socio–economic solutions to the issue of personnel training for the national economy. The article examines the advantages and disadvantages of creating new campuses, examines the problems of substantiating the reasons for the existence of campuses, the goals and objectives of the functioning of campuses, provides the structure of subsidies for the development of urban tourism infrastructure, taking into account the construction of new type campuses. The experience of creating and financing university campuses in the subjects of the Russian Federation has been studied. Conclusion. As a result of systematization of organizational conditions, advantages and disadvantages of new-type campuses, a conclusion is made about the need for rational financing in projects for the creation of newtype campuses in pilot subjects of the Russian Federation. The main purpose of this is the emergence of additional educational and experimental production sites used to introduce the results of science into the practice of the national economy.